Pengujian Struktur Mikro Pada Kekuatan Tarik dan Bending pada Sambungan Las Terhadap Pengelasan Material Baja SS400 - Yanuar, Setiyo Ferdi; Nely Ana Mufarida; Moch. Arif Wibowo (Universitas Muhammadiyah Metro, 2024)
The welding process is widely used for joining in machine construction and steel construction. One popular welding method today is SMAW. SMAW welding is effective and practical because it only requires simple tools and electrodes in its use. The purpose of this study is to determine the effect of different welding currents on the cooling liquid on the welding results of SS400 steel material. This study uses SMAW welding with an E6013 Ø2.6mm electrode and SS400 steel material. After welding, the specimens were immersed in cooling liquids, namely 10% dromus, radiator coolant, and SAE 40 oil. The results of the research on the SMAW welding process for SS400 steel showed that immersion using SAE 40 oil produced the highest tensile strength at both 80A and 90A currents, which were 28.79 kg/mm2 and 28.22 kg/mm2, respectively. Meanwhile, the bending test results showed two different outcomes: at 80A current, immersion welding using radiator coolant produced the highest bending strength at 1067.77 kgf/mm2, whereas at 90A current, immersion welding using dromus produced the highest bending strength at 1130.22 kgf/mm2.